Oncoplastic surgery in elderly patients with breast cancer: overtreatment or a goal worth pursuing? - Stefano Chiodi; Ugo Catrambone; Giuseppe Verrina; Andrea Decensi; Pamela Guglielmini; Marco Filauro (Geriatric Care, 2016)
Breast cancer is the most common cancer in women in Western countries, which increases with age. The improvement of reconstructive methods in light of the principles and techniques borrowed directly from cosmetic surgery has helped raise the quality in terms of aesthetic results in conservative treatment. This approach has reached results, which merits a more precise role of self-autonomy and the name of oncoplastic breast surgery. Today this approach is becoming, in the centers dedicated to the treatment of breast cancer, the gold standard in the surgical treatment of patients with this cancer. So if the role of oncoplastic in the surgical treatment of breast cancer is to be established, it remains crucial to have a selection of patients who could benefit from this approach: today, age is one of the determining factors in the selection of patients and, in fact, patients over 75 years, are often excluded from surgery of this type. In our opinion, after a multidisciplinary assessment, also the older women could be able to receive this type of surgical approach.